Generation Z and the World of Work in Southeast Asia: A Bibliometric Study and Systematic Literature Review 20152025 - Sipayung, Maurits Sahata (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to map the development of research related to Generation Z in the world of work through a combination of bibliometric methods and systematic literature review (SLR). A total of 609 articles were analyzed using a bibliometric approach to identify trends, scientific contributions, and conceptual strength of the articles. From the mapping results, eight main clusters were found, organizational climate and work well-being; generational comparison and entrepreneurial behavior; career adaptability and employer perceptions; strategies for understanding Gen Z in the world of work; psychological capacity and work values; personal potential and financial literacy; the COVID-19 pandemic and its impact and technology and Gen Z digital behavior. SLR findings from 80 selected articles reveal dominant topic trends and suggest future research directions, namely: Work Values Work World Preferences; Entrepreneurial Orientation Financial Readiness; Workplace Well-Being and Organizational Climate; Digital Engagement Technology Adaptation; and Social Awareness, Inclusion, and Community Engagement. This research provides a conceptual contribution in the form of a thematic framework that can be used as a reference in developing cross-disciplinary research related to Generation Z, especially in the very diverse and dynamic social, cultural, economic, and geopolitical context of Southeast Asia.